Catalyzing Diabetes Prediction: Harnessing Machine Learning and Deep Learning for Optimization and Clustering - Monelli Ayyavaraiah (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Diseases like diabetes mellitus are highly worrying since they kill so many people every year. High blood sugar levels are the root cause of this chronic condition. Untreated diabetes just adds extra complications to the lives of those who have it. Therefore, the mortality rate of humans may be lowered by the early prediction of diabetes. Diabetes may be better diagnosed using the data mining approach. Data mining methods for early prediction and illness detection described in a number of publications have varying degrees of accuracy. At the same time, data security is a major concern when mining information on diabetes. To address this problem, this paper develops a novel model for accurate early prediction of diabetes. In the first phase of the study, improved principal component analysis is investigated for its potential use in extracting useful features from the dataset. The machine learning approach proposes a Modified Support Vector Machine (MSVM) to diagnose diabetes at an early stage since it has the best accuracy of classification. Mining the patient’s illness findings in the cloud is the key contribution of this study. The honey bee encryption and decryption algorithm is employed for this purpose. The accuracy, sensitivity, specificity, precision, and Negative Predictive Value (NPV) of the suggested approach are assessed using a number of different metrics. The collected results demonstrate the superiority of the suggested MSVM classifier, with an accuracy of 97.13%. The superior performance of the suggested approach has been shown by comparing it to the state of the art.